Analytical kinetic block model of crystal-mother-phase multilayer interface. - Organiściak, Maciej; Izdebski, Marek; Ledzion, Rafał (Wydawnictwo Politechniki Łódzkiej, 2015)
Simple kinetic block model of multilayer crystal-mother-phase interface is proposed. The model leads to a system of differential equations which can be solved without the need to run Monte Carlo simulations. The proposed model is based on Bragg-Williams approximation (called also zeroth-order approximation), "solid-on-solid" assumption, and other assumptions common with thermodynamic Temkin model. Thus, it is possible to test the compliance of kinetic and thermodynamic approaches in a situation where all other significant differences between models are eliminated. Moreover, a comparison with the results of kinetic Monte Carlo simulations allows for better understanding of the impact of Bragg-Williams approximation.

Zaproponowano prosty kinetyczny blokowy model wielowarstwowej granicy faz kryształ-faza macierzysta. Model ten prowadzi do układu równań różniczkowych, które rozwiązuje się bez potrzeby przeprowadzania symulacji Monte Carlo. Zaproponowany model wykorzystuje przybliżenie Bragga- Williamsa (zwane także przybliżeniem zerowego rzędu), założenie znane w literaturze jako „solid-on-solid” oraz inne założenia wspólne z termodynamicznym modelem Temkina, co umożliwia sprawdzenie zgodności podejścia kinetycznego i termodynamicznego w sytuacji gdy nie występują inne istotne różnice pomiędzy modelami. Ponadto porównanie zaproponowanego modelu z kinetycznymi symulacjami Monte Carlo umożliwia lepsze zrozumienie znaczenia przybliżenia Bragga-Williamsa.
Analityczny kinetyczny model blokowy wielowarstwowej granicy faz kryształ-faza macierzysta.
Institute of Physics, Faculty of Technical Physics, Information Technology and Applied Mathematics. Lodz University of Technology
Instytut Fizyki, Wydział Fizyki Technicznej, Informatyki i Matematyki Stosowanej, Politechnika Łódzka
Keywords: crystal-mother-phase interface; Temkin’s model; kinetic block model; Bragg-Williams approximation; kinetyczny model blokowy; kryształ-faza macierzysta; przybliżenie Bragga- Williamsa; modelem Temkina